Design and Development of Sidajaya Tourism Village Information System as a Mobile-based Information and Promotion Media - Iqbal, Mohammad; Vernanda, Dwi; Rosid, Usep Abdul; Hanan, Ardian abdul; Riyanto, Brilian Adiguna; Virtalioka, Sheva (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2025)
The potential of Sidajaya Tourism Village in Subang Regency is still not widely known by the people of Subang, which has hindered the development and progress of the tourism village. The limited availability of information has made people reluctant to seek further details, leading to a lack of widespread knowledge about Sidajaya Tourism Village. Therefore, a mobile system is needed to facilitate public access to information about this tourism village. This study aims to build a mobile-based information system that can serve as a medium for disseminating information and promoting Sidajaya Tourism Village. The information system will be developed using Android Java programming language and MySQL database. Data will be collected through observation and interviews, which will then be processed into a system analysis of the current system and the proposed one. The system development stages include analysis, system design, implementation, and testing. The application that is developed will allow the public to access tourism information and book tickets for the various tourist spots in Sidajaya Tourism Village.